Reconstructing the Climate Variability During the Last 5000 Years From the Banni Plains, Kachchh, Western India - Makwana, Nisarg; Prizomwala, S. P.; Das, Archana; Phartiyal, Binita; Sodhi, Aashima; Vedpathak, Chintan (Frontiers in Earth Science, 2021)
The climatic conditions during the beginning of the last 5,000 years have been discussed, debated, and documented from various parts of the Indian subcontinent, due to the human–climate interrelationship. In the present study, we report a multi-proxy dataset encompassing the widely used ∼ geochemical and mineral magnetic proxies supported by radiocarbon and optical chronologies from the Banni Plains of the Rann of Kachchh, western India. Our results support the earlier observations of the prolonged wetter climatic condition synchronous with the mature phase of Harappan era which witnessed a short and intense arid condition at the terminal part of the mature Harappan phase. The climate system dramatically fluctuated during the last five millennia from pulsating between relatively arid (4,800–4,400 years BP, 3,300–3,000 years BP, and at 2,400 years BP) and relatively humid phases (>4,800 years BP, 4,000–3,300 years BP, 1900–1,400 years BP, and 900–550 years BP). The multi-proxy dataset shows a gradual strengthening of the monsoonal conditions from the Banni Plains during the late Harappan phase. Apart from this, the high sedimentation rate (>1 mm/yr) recorded from the Banni Plains suggests it can be tapped as a robust archive to reconstruct multi-decadal to centennial climatic events spanning the Holocene epoch.